Financial and Sports Results of Public Sector Enterprises Operating Professional Sports Clubs - Wyszyński, Artur (Olsztyn Economic Journal, 2023)
This article analyses the extent of state ownership and examines whether there are differences in business and sports activity results between state-owned and private entities running football clubs in the Polish Ekstraklasa. The study examined a panel of 100 entities (N) comprising 26 enterprises running football clubs whose male teams participated in Ekstraklasa games during five seasons: 2016/2017, 2017/2018, 2018/2019, 2019/2020 and 2020/2021. The study covered five consecutive financial years ending in 2017, 2018, 2019, 2020 and 2021. The statistical and financial analysis method was applied. The financial and sports results of state owned and private enterprises in the period of 2017-2021 were compared based on selected ratios. The mean and median values of the variables taken for analyses (financial and sports ratios) were calculated. A non parametric Kruskal-Wallis test was applied to assess the differences between the ratios for the groups of enterprises under study. The analysis revealed that state-owned companies and local government units are major shareholders in Polish professional football clubs. Examination of the financial results of public and private enterprises that run such clubs revealed statistically significant differences between most of them. Among the three groups of enterprises, those run by local government enterprises achieved the worst financial results measured by profitability, financial liquidity, debt, team cost and equity. The best financial situation was observed in the state-owned enterprises. Although no statistically significant difference was found in the sports achievements between the groups of clubs, the privately owned enterprises had better results (the median and the mean values) than the other enterprises concerning the number of points and a higher place at the end of the season.